Islamic Bank peformance based on Maqasid Based Performance Evaluation Model (MPEM) - Mustika Noor Mifrahi; Faaza Fakhrunnas (Jurnal Ekonomi & Keuangan Islam, 2018)
This study aims to measure the performance of Sharia banking under Maqashid Shariah’s point of view. Maqashid-sharia-based Performance Evaluation Model (MPEM) approach does not only shows the overall banking performance as usual, but also in the aspect of its Sharia compliance. The samples used in this study are 11 Islamic banks which is retrived from Central Bank of Indonesia that consist of Islamic Bank’s annual report from 2011 to 2017. To measure the Islamic banks, this research adopts maqashid sharia measurement that consist of 5 (five) elements formulated in MPEM. According to the finding, Bank Muammalat Indonesia (BMI) outperforms in all aspects with an average value of 177,93. However, in detail each Islamic banks has its strength in different criteria. Eventhough in certain period Islamic banks suffered loss, this condition did not lead the bank to perform non sharia activity.